Scaffold development to engineer human intestinal epithelial tissue grafts - Chandaria, Rehma (2017)
Epithelial crypts isolated from normal colon mucosa have been cultured in vitro in the form of organoids. These organoids have been shown to have regenerative potential when implanted in mouse models of denuded colon mucosa. However, a major limitation in the translation of these studies to a clinical setting is the use of Matrigel, which is clinically unsuitable due to its undefined composition and potential for tumourigenicity. Additionally, enclosed organoids do not fully reproduce the structure and function of native tissue, and do not lead to full integration into the host. Therefore, the overall aim of this thesis was to investigate different scaffolds for their ability to support growth of primary colon epithelial cells in order to form an open monolayer structure that resembles native epithelium. It was anticipated that in vitro culture of primary colon cells would be more efficient with isolated stem cells than with an entire heterogeneous epithelial cell population. Therefore, the side population technique was explored using established cell lines as a method of isolating a population enriched in stem cells, based on their ability to efflux the Hoechst 33342 dye. This was found to be irreproducible and unreliable so was not pursued further. Various scaffolds were manufactured, characterised and seeded with colon epithelial cell lines to investigate how their morphological and biochemical characteristics influenced cell proliferation and differentiation. Electrospun nanofibre and microfibre scaffolds made from the synthetic material PET, and the natural polymer gelatin were fabricated. All electrospun scaffolds supported proliferation, and cells on gelatin nanofibre scaffolds differentiated to form tight junctions that are typical of epithelial cells, while also expressing increased levels of the stem cell marker ABCG2. Thereby, gelatin nanofibres demonstrated the ability to support appropriate cell differentiation while maintaining a pool of stem cells. Gelatin in the form of hydrogel scaffolds was also investigated for its ability to support cell proliferation and influence cell differentiation. Moreover, a novel method of rapidly 3D printing scaffolds using unmodified gelatin was presented. Both planar and 3D gelatin scaffolds were able to support proliferation and tight junction formation in Caco2 cells. Thus, it was concluded that gelatin hydrogels are a suitable substrate for proliferation and differentiation of colon carcinoma cell lines, and that the addition of the printed topography did not have any negative effects on cell growth and behaviour. Epithelial crypts were isolated from human colon mucosa and expanded in vitro in the form of organoids, as previously published. It was found that the precise nature and source of organoid media components are critical for successful primary cell culture. A method in which the Wnt signalling cascade is indirectly activated by GSK3β inhibition was found to be partially successful for growing organoids and may be a potential alternative culture method. Primary organoid cells were seeded onto gelatin nanofibre and hydrogel scaffolds, however the cells did not proliferate in these preliminary experiments. Overall, it was concluded that although the gelatin scaffolds demonstrated promising results with colon carcinoma cell lines, more research would be required in order to produce scaffolds that can support growth of primary colon epithelial cells.